Pengaruh Pengalaman Praktik Kerja Lapangan dan Prestasi Akademik yang Dimoderasi oleh Keaktifan Mahasiswa dalam Berorganisasi Terhadap Kesiapan Mahasiswa dalam Memasuki Dunia Kerja - Rinda Sari; Rita Syofyan (Jurnal Ecogen, 2021)
Abstract : The purpose of this research is to find out the influence of fieldwork experience and academic achievement moderated by students' activeness in organizing towards the readiness of Faculty of Economics students in 2016 in entering the world of work. This type of research is kausative. The population in this study was students of the Faculty of Economics in 2016. The number of research samples as many as 100 people and selected using the technique Proportional Random Sampling. The analysis method used is Moderated Regression Analysis (MRA) using SPSS 16. The results of the study showed that (1) experience of field work practices significantly influenced the readiness of Faculty of Economics students in 2016 in entering the world of work, (2) academic achievement had a significant influence on the readiness of students of the Faculty of Economics in 2016 in entering the world of work, (3) experience of field work practice moderated by student activity in organizing significantly influenced the readiness of Faculty of Economics students in 2016 in entering the world of work , (4) academic achievement moderated by the activeness of students in organizing has a significant effect on the readiness of students of the Faculty of Economics in 2016 in entering the world of work. Keywords: experience of fieldwork practices, academic achievement, activeness of students in organizing and readiness to enter the world of work